2019
DOI: 10.1002/star.201800284
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Octenylsuccinylation of Oxidized Cassava Starch on Grease Resistance and Waterproofing of Food Wrapping Paper

Abstract: The surface of food wrapping paper is coated with octenylsuccinic anhydride (OSA)‐modified cassava starch to develop food packaging with high waterproofing and low grease permeability. Oxidized cassava starch is modified using various concentrations of OSA, and esterification is confirmed by Fourier transform infrared spectroscopy (FT‐IR) and 1H nuclear magnetic resonance spectroscopy (1H NMR). To explore the effects of OSA concentration, starch content, incubation time, and coating rate on oil resistance and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…This is consistent with Parker et al (2005), who showed that ring crush strength increased with increasing density of handsheets. (Zhong et al 2019). Figure 7 shows the Cobb60 data for the handsheets and indicates that water resistance could be increased by consolidating the fibrous networks by increasing hemp fiber content and hot-pressing.…”
Section: Ring Crush Test (Rct) Indexmentioning
confidence: 99%
“…This is consistent with Parker et al (2005), who showed that ring crush strength increased with increasing density of handsheets. (Zhong et al 2019). Figure 7 shows the Cobb60 data for the handsheets and indicates that water resistance could be increased by consolidating the fibrous networks by increasing hemp fiber content and hot-pressing.…”
Section: Ring Crush Test (Rct) Indexmentioning
confidence: 99%
“…For example, previous patents claimed starches esterified with ASAs have improved grease resistance but did not elaborate on water resistance (Mackewicz et al., 2002; Tippit, 2011). A recent study of starch octenylsuccinate coatings on paper found small improvements in both grease and water resistance as the level of octenylsuccinic anhydride (OSA) increased from 0% to 3% (Zhong et al., 2019). Paper coated with starch ester dispersions having much higher degree of substitution (DS) in the range of 1 to 2 have much improved water resistance (Billmers & Sweeney, 2000).…”
Section: Surface Sizingmentioning
confidence: 99%
“…Paper is also a natural high-grade packaging material that allows for sustainable development. 6 As a food packaging material, however, the paper needs additional processing to confer antibacterial and preservative properties, as well as oil and water resistance. Ceramic paper is a new type of paper that can be prepared by the coating method, using ceramic slurry as the pigment.…”
Section: Introductionmentioning
confidence: 99%
“…Paper‐based packaging materials have a number of advantages, including wide availability of raw materials, good printing performance, low processing costs and lack of toxicity. Paper is also a natural high‐grade packaging material that allows for sustainable development 6 . As a food packaging material, however, the paper needs additional processing to confer antibacterial and preservative properties, as well as oil and water resistance.…”
Section: Introductionmentioning
confidence: 99%